Impact of Climate Change on Vegetable Production and its Technologies for Mitigation - Sharma, Pallavi; Singh, Shiv Pratap; Kumari, Manisha (International Journal of Economic Plants, 2023)
Agriculture sector is the most sensitive sector to the climate change because the climate of a region determines the nature and characteristics of vegetation and crops. A significant change in climate on global scale will impact vegetation and consequently affect the world’s food supply. Vegetables play a crucial role in ensuring food and nutritional security, but they are highly perishable and their prices rise fast under changing climate conditions. Climate change is an unavoidable phenomenon of natural and anthropogenic origin against which mitigation is required to reduce the risk in vegetable production. For mitigating the impact of climate change various technologies such as developing climate resilient varieties, agronomic practices, integrated cropping systems, organic farming, cultural management, protected cultivation, forecasting and simulation models are used. Agronomic practices such as resource conservation technologies mitigate atmospheric greenhouse gases by reducing the existing emission sources and sequestering carbon through minimal soil disturbance. Organic farming, protected cultivation, carbon sequestration by cropping system and agroforestry provide a suite of possible strategies for addressing the impact of climate change on vegetable production. Screening the available germplasm for the heat tolerance, drought tolerance and salinity tolerance and using these tolerant genotypes in the breeding programme is one of the feasible options to combat climate change. In addition, weather forecasting models and growth simulation models can be used to predict the possible impact of climate change and to mitigate its effect on vegetable crop production.